Pengaruh Persepsi Manfaat Penggunaan QRIS Terhadap Keputusan Pembelian Ayam Geprek Sriwedari: Survei pada Pelanggan Ayam Geprek Sriwedari - Muhammad Rizki Ramadhan; Muhammad Daffa Jauza Fikri; Abdul Yusuf (Masyarakat Ekonomi Syariah Bogor, 2024)
Technological developments have had a very broad impact on various aspects of life, one of which is being adopted by the financial industry. The presence of QRIS or Indonesian Standard Quick Response Code provides a new style in transactions, because users no longer need to make payments in cash, just by scanning the barcode, payments can easily be made, of course with a payment model like this provides convenience, security and satisfaction in transactions. This also applies to the transaction of purchasing Sriwedari fried chicken which is a student favorite in the East Telukjambe area. The use of QRIS is widely used by the millennial generation among students. Therefore, this research aims to review and find out more about the perception of the benefits of using QRIS in chicken purchasing decisions. smashed Sriwedari. The research was carried out using a descriptive quantitative method by collecting data using a questionnaire distributed to respondents. The number of respondents in this study was 103 respondents who were taken randomly with the criteria of purchasing Sriwedari fried chicken at least once a week. The results of the research show that the magnitude of the influence of the perceived benefits of using QRIS on purchasing decisions is 59.7% and the perceived benefits (X1) of using QRIS on purchasing decisions (Y) Sriwedari fried chicken has a simultaneous and positive effect.